Transformations of Words and Their Impact on the Dialogue of Reality and its Criticism, Abdul Razzaq Al-Amiri as An Example - Wans , Zaman Mohamed; Anooz , Sabah Abbas (Journal of Ecohumanism, 2024)
The transformations of words help reveal the role of dialogue in the semantic structure of literary texts. It is a language that sometimes glows with metaphor, and its meaning is amplified through deviation, intensification, and ambiguity at other times. It breaks the self-referential mode of discourse into a dialogue composed of two or more parties in the poetic text. This leads to the transformation of the text from its self-purpose to a purpose that involves addressing the surrounding reality of the writer in a displaced poetic language. This gives his discourse a multiple semantic interpretation in the mysterious meanings characterized by a dramatic nature. This is not limited to major events, as every incident from our daily lives, even if it is partial, and every glance and every word, is a dramatic structure regardless of its size. So, how does the poet use that incident?! By doing so, he naturally differs from ordinary people, as he incorporates it into his poetic language and engages in a dialogue with his reality in forms that attract the attention of the recipients.